Prevalence of sports injuries in Korean fencers aged 14-40 years - Chung, J. W.; Lim, B. O.; Cho, J. H.; Lee, K. H. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: Although sites and types of injury frequently occurring in fencers have been well described, the type of injury caused by the use of fencing movements is still unknown. This study aimed to provide basic data for injury prevention by understanding the sports injury status in fencers. METHODS: A total of 584 South Korean fencers were included in the survey and were classified according to the injured site, cause of injury, and movement that causes injury. The collected data were analyzed using frequency analysis, Chi² tests, and logistic regression analysis to identify differences in sex, event type, age, and career. RESULTS: Female (P=0.001) and foil fencers (P=0.015) were more likely to experience injury than male and sabre and epee fencers. The incidence of injury was significantly higher according to age (P=0.001) and career (P=0.001). The ankle was the most frequently injured site (17.71%). Injuries most frequently occur during Fente movement (48.11%). Insufficient warm-up was the most common cause of injury (23.91%) in all groups. CONCLUSIONS: These results suggest that a specific warm-up program and strengthening exercises of the ankle and knee ligaments should be established to prevent injuries for fencers. Particularly, female, foil, adult, and experienced fencers should be more careful in preventing injuries.